The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4254/wjh.v2.i7.275
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric nonalcoholic fatty liver disease: A clinical and laboratory challenge

Abstract: The true prevalence of pediatric nonalcoholic fatty liver disease (NAFLD) is unknown. Challenges in determining the population prevalence of NAFLD include the type of test (and the reference intervals used to define normal and abnormal), the type of population (general population, hospital series), the demographic characteristics of the population sampled, and the nature of the study design. The natural history of pediatric NAFLD remains uncertain. The issue of when to perform a liver biopsy in children with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 137 publications
3
27
1
Order By: Relevance
“…The sensitivity of this biochemical marker, however, remains low because a number pediatric patients may present ALT values in the normal range [29] . Moreover, given the clinical relevance of identifying children with steatohepatitis (NASH), several studies have described biomarkers associated with pediatric NASH [29,30] . Patton et al [30] , evaluating clinical relation of histopathology with transaminases in pediatric NAFLD, found that AST was superior to ALT in distinguishing NAFLD patterns, while other studies showed ALT performing better [12,15,24] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensitivity of this biochemical marker, however, remains low because a number pediatric patients may present ALT values in the normal range [29] . Moreover, given the clinical relevance of identifying children with steatohepatitis (NASH), several studies have described biomarkers associated with pediatric NASH [29,30] . Patton et al [30] , evaluating clinical relation of histopathology with transaminases in pediatric NAFLD, found that AST was superior to ALT in distinguishing NAFLD patterns, while other studies showed ALT performing better [12,15,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Patton et al [30] , evaluating clinical relation of histopathology with transaminases in pediatric NAFLD, found that AST was superior to ALT in distinguishing NAFLD patterns, while other studies showed ALT performing better [12,15,24] . Indeed, it is now widely accepted that the degree of ALT elevation does not correlate with the presence or severity of histological findings of NAFLD [29] . For this reason in the present study we considered not only the transaminases value at baseline and at the end of treatment but also the change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the prevalence of obesity among US children has tripled in just one decade, rising from 5 % in 1980 to 15 % in 1990 and is currently around 17 %(Centers for Disease Control and Prevention CDC, 2011). The estimates of NAFLD prevalence in childhood have risen accordingly and are already between 2.6 and 9.6 % among the general pediatric population (Pacifico et al, 2010), reaching 68 % in obese children (Fu et al, 2011). Most cases of NAFLD arise in the detrimental environment of various metabolic disorders commonly known as the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%